2007
DOI: 10.1007/s10493-007-9066-1
|View full text |Cite
|
Sign up to set email alerts
|

Repellency of methyl jasmonate to Ixodes ricinus nymphs (Acari: Ixodidae)

Abstract: In our search for tick repellents of plant origin, to be used as alternatives to commercial arthropod repellents, we investigated the effect of the well known plant signaling compound methyl jasmonate (MJ) using nymphs of the tick Ixodes ricinus. In laboratory tests, pieces of cloth with MJ at 0.075, 0.15, 0.30 and 0.75 mg/cm2 yielded increasing repellencies against the nymphs: 57%, 71%, 92% and 99%, respectively, of the nymphs did not cling to the cloth. Repellency of MJ was also investigated in a tick-infest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…After all, DEET, a more recent synthetic counterpart developed by molecular modeling (2), picaridin, and methyl jasmonate share similar structural motifs, which are essential for activity (20), and methyl jasmonate is a repellent for the southern house mosquito, as well as ticks (21). CquiOR136•CquiOrcoexpressing oocytes challenged with methyl jasmonate generated strong responses, whereas jasmonic acid elicited very low responses (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, DEET, a more recent synthetic counterpart developed by molecular modeling (2), picaridin, and methyl jasmonate share similar structural motifs, which are essential for activity (20), and methyl jasmonate is a repellent for the southern house mosquito, as well as ticks (21). CquiOR136•CquiOrcoexpressing oocytes challenged with methyl jasmonate generated strong responses, whereas jasmonic acid elicited very low responses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4). Jasmonic acid is a nonvolatile compound and, therefore, unlikely to repel at a distance, whereas methyl jasmonate has the ideal vapor pressure for a repellent (3.37 × 10 −4 mmHg at 25°C; toxnet.nlm.nih.gov), is released by injured plants (19), and has been demonstrated to be a repellent (21). Indeed, we observed in our surface-landing and feeding assay that methyl jasmonate is a repellent for the southern house mosquito (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, with the exception of several studies that tested treated drags against Dermacentor variabilis (Say) (Granett and French 1950) and I. ricinus L. Garboui et al 2006Garboui et al , 2007, these sampling methods have not been routinely used to Þeld test repellents. In these preliminary trials, we found that tick drags and CO 2 traps were useful screening techniques for Þeld-testing the relative effectiveness of several repellents over time and that they met the criteria suggested by Bissinger and Roe (2010) of being easy to perform, rapid, and inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers, especially those testing botanicals as repellents, have found or suggested that formulation is essential for stability, persistence and activity (Jaenson et al, 2006;Carroll et al, 2007;Garboui et al, 2007;Moore et al, 2007). For example, Schreck et al (1995) evaluated unformulated DEET against nymphal A. americanum at an application rate of 0.3 mg/cm 2 on human skin and reported that repellency dropped to <90% approximately 2.7 h after treatment.…”
Section: Discussionmentioning
confidence: 99%